2021
DOI: 10.2478/amns.2021.1.00019
|View full text |Cite
|
Sign up to set email alerts
|

Research on space optimization of historic blocks on Jiangnan from the perspective of place construction

Abstract: In the process of rapid urbanization, gentrification and commercialization have inevitably appeared in the historical districts of Jiangnan. Although they optimize the space environment of the historic district and promote the development of economy and tourism, they have resulted in disadvantages such as insufficient vitality of the space group, rigid space interface, lack of space quality and lack of regional culture. Mathematical calculation can be used to analyse the data of 15 historical blocks, determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The digital ecology not only provides rich data resources, but also offers new perspectives on the sustainable development of rural B&Bs through the application of algorithms. The result exists a consistent recognition with the optimal row design of neighborhood houses proposed by Teng Y et al [24]. Finally, the innovation of spatial planning and design, the study is able to solve the complex problems in spatial planning of rural lodging more effectively by utilizing the Bert-BiLSTM-EIC algorithm.…”
Section: Discussionsupporting
confidence: 73%
“…The digital ecology not only provides rich data resources, but also offers new perspectives on the sustainable development of rural B&Bs through the application of algorithms. The result exists a consistent recognition with the optimal row design of neighborhood houses proposed by Teng Y et al [24]. Finally, the innovation of spatial planning and design, the study is able to solve the complex problems in spatial planning of rural lodging more effectively by utilizing the Bert-BiLSTM-EIC algorithm.…”
Section: Discussionsupporting
confidence: 73%
“…Considering a robust multiobjective mathematical model and optimizing stock portfolio are the superiority of this study over Meng-Ren et al [47]; Liu et al [48]; and Luo et al [49]. Also, considering the objectives such as maximizing returns, maximizing liquidity, and minimizing risk are the superiorities of this study over those of Wu et al [50] and Teng et al [51].…”
Section: Discussionmentioning
confidence: 86%
“…The architectural colors of historical areas often retain their original color features, such as old red brick walls, time-honored blue flagstone (Qingshiban) pavement, and unique local cultural colors [13]. These color features are an important reflection of the color authenticity of historical areas and are also an important component of their historical and cultural value [14]. In the study of architectural color in historical areas, it has been found that different historical periods, geographical environments, and cultural backgrounds can all affect the architectural colors of historical areas [15].…”
Section: Color Authenticity Of Historical Areasmentioning
confidence: 99%